SAVING A NATION, S SOUL. - Fitzwilliam, Helen (World Today)
The article addresses efforts to protect cultural treasures in Ukraine amid the Russian invasion of the country. Topics discussed include information on the campaign, called Saving Ukrainian Cultural Heritage Online, which will record and preserve a culture they fear Vladimir Putin's Russia wants to erase, and consequences of the failure to defend museums and monuments during the wars in Iraq, Afghanistan and Syria, according to Peter Stone, a professor of Heritage Studies.